Clinical practice of e research nurse - Ribeiro, Patrícia Graziela Cunha (2018)
This paper proposes to present the main activities of a Research Nurse, its role in clinical research, and in the development and introduction of new drugs on the market. The Master in Pharmaceutical Medicine brought together knowledge and development of new technical and personal skills extremely valuable in daily activity as research nurse. During my professional activity as a research nurse, were detected many gaps in academic and professional training of nurses, with regard to this specific area. I intend to present a personal view, describing the main activities developed and how the knowledge acquired in this Master influenced my work performance. The main objective of this work is to provide a reference or guide to other nurses who want to enter into the area of clinical research.